The Determinants of Central Government Financial Report Quality In Indonesia: The Moderating Role of The Internal Control System - Triana Meinarsih; Abdul Yusuf (Jurnal Reviu Akuntansi dan Keuangan, 2026)
Purpose: This study examines the effects of accrual-based government accounting (SAP), the quality of the State Civil Apparatus (ASN), and public accountability on the quality of financial reports, with the Government Internal Control System (SPIP) as a moderating variable. Grounded in agency theory, the study frames government agencies as agents obligated to report accurately to the public as principal. Methodology/approach: A quantitative survey design was employed. Structured questionnaires were distributed via Google Form through official KPPN email channels and physical distribution at KPPN coordination meetings, to 518 respondents across 34 ministries and agencies managing APBN funds throughout Indonesia. Hypotheses were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0, encompassing outer model assessment (measurement model) and inner model assessment (structural model) with bootstrapping (5,000 subsamples) for significance testing. Sample adequacy was verified using G*Power 3.1. Findings: All three exogenous constructs — accrual-based government accounting, ASN quality, and public accountability — positively and significantly influence financial report quality (R² = 0.754). SPIP significantly strengthens the positive effects of accrual-based accounting and public accountability, but does not significantly moderate the effect of ASN quality. Practical implications: Leaders and stakeholders should strengthen SPIP implementation, improve ASN competencies through targeted accounting training, and enhance budget planning and accountability practices to produce higher-quality financial reports. Originality/value: This study contributes novel evidence from a large national sample of APBN-managing work units on the moderating role of SPIP, grounded in agency theory, within Indonesia's central government financial reporting context.